Multimedia and Game-Based Approaches in Vocabulary Instruction: A Study on Young EFL Learners Using YouTube and Taboo Games - Rhika Sary Amriyanti; Nurteteng (TEKILA: Journal of Language Teaching and Literature, 2025)
This study investigates the effectiveness of integrating YouTube videos and the Taboo game in improving vocabulary acquisition among young EFL learners at SD Muhammadiyah Aimas. The study aimed to determine whether the combination of multimedia learning and game-based activities could enhance students’ vocabulary mastery and engagement in the learning process. A quantitative approach was employed using a pre-experimental one-group pre-test and post-test design involving 20 fourth-grade students from Class IVA. Data were collected through vocabulary tests consisting of multiple-choice and matching items administered before and after the intervention. The collected data were analyzed using SPSS to examine descriptive statistics and conduct a paired sample t-test. The results indicate a substantial improvement in students’ vocabulary performance after the implementation of the instructional strategy. The mean score increased from 50.75 in the pre-test to 80.75 in the post-test, demonstrating a significant gain in vocabulary mastery. The paired sample t-test produced a p-value of 0.000, which is lower than the significance level of 0.05, indicating a statistically significant difference between the pre-test and post-test scores. These findings suggest that the integration of YouTube videos and the Taboo game provides an effective learning environment that supports vocabulary development among young learners. The use of YouTube videos provided rich audiovisual input that helped students understand vocabulary through contextualized visual and auditory cues, while the Taboo game encouraged active participation, collaboration, and vocabulary retrieval during classroom interaction. Together, these approaches created an engaging and student-centered learning atmosphere that increased motivation and participation in vocabulary learning activities. The integration of multimedia learning and game-based instruction can effectively enhance vocabulary acquisition among young EFL learners. The findings highlight the potential of combining digital media and interactive games as an innovative strategy for vocabulary instruction in elementary school contexts. Future studies are recommended to involve larger participant groups and explore different vocabulary categories to further validate the effectiveness of this approach.